Penerapan Desain Grafis Dalam Memasarkan Aplikasi Bangbeli Guna Meningkatkan Pendapatan Mitra Bisnis Pelaku UMKM di PT. Doa Anak Digital (Bangbeli) - Abdillah Hanif Isna S; Maharani Ikaningtyas (Lembaga Pengembangan Kinerja Dosen, 2023)
Along with the times and increasingly advanced technology, people are increasingly aware of the importance of information needs. The digital and internet worlds are also having an impact on the marketing world, with companies and organizations increasingly realizing the importance of an integrated marketing strategy. Digital marketing can make it easier for business people to monitor and provide for all the needs and wants of potential customers. There are various ways to market products through social media, one of which is graphic design. Graphic design itself is used to convey messages that are right on target with the concept of communication and creativity using various media and techniques. The purpose of this project is to apply graphic design in marketing the Bangbeli application which is expected to help restore the community's economy, especially MSME players as business partners to earn additional income. In this project the author uses a results dissemination scheme by sharing the knowledge and experience gained with the community so that it can be utilized more widely by the community. World Health Organization., (2018), according to him the dissemination of results is a process of communicating information related to research or findings to relevant stakeholders to inform policies, practices, and decision making. The results of this project are expected to encourage new breakthroughs for the community in the form of applications that can provide additional income from home.